EFEK BEBERAPA JENIS OBAT TERHADAP JARINGAN PERIODONTAL: TINJAUAN PUSTAKA - Sitti Raoda Juanita R; Mardiana Adam (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction: The main etiology of periodontal disease is the presence of dental plaque and poor oral hygiene. This condition can be exacerbated through systemic drug therapy by modifying the inflammatory and immunological responses of periodontal tissue to bacterial plaque. In addition to the use of systemic drug therapy, the use of illicit drugs also affects changes in periodontal tissue. The prevalence of drugs has increased globally. Understanding the effects of drugs on periodontal tissue helps clinicians determine diagnoses and treatment plans. This article aims to understand the medication affecting the changes of periodontal tissue. Review: The literatures were obtained using a variety of different database sources (Medline via PubMed, Wiley Online Library, and Google Scholar), with the keyword systemic drugs AND periodontal tissue; Illicit drugs AND periodontal disease; recreational drugs AND periodontal disease; sex hormone AND periodontal tissue. This literature outlines the various periodontal tissue changes as an effect of systemic drug therapies including anti-hypertensive, anti-convulsion, immunosuppressant, anti-inflammatory, hormones and sedatives such as cannabinoids, opioids, stimulants, and hallucinogens. Periodontal tissue changes can be exacerbated by drug interactions, both systemic therapy drugs and illicit drugs. Some studies have found an association between systemic drug consumption and the patient's periodontal condition. Some medications have different effects on periodontal tissue which affect the time and type of periodontal treatment. Conclusion: Understanding the effect of drugs on periodontal tissue helps the clinician determine diagnoses and treatment plans that are appropriate for the patient's periodontal condition.